2019
DOI: 10.22364/bjmc.2019.7.1.06
|View full text |Cite
|
Sign up to set email alerts
|

Key Drivers of Digitalization; EU Context and Baltic Case

Abstract: The integrated Digital Economy and Society Index (DESI) is calculated to indicate "progress of EU countries towards a digital economy and society"; nevertheless there are serious barriers to practical use of the DESI. The methodology of the DESI does not apply to development indicators; the natural doubts are on significance of more than 30 aspects for socioeconomic growth. The study propose the methodology for determination of the key drivers of digitalisation, hence areas of priority investments, which can p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…Algorithms of regression analysis and benchmarking were applied to explore cause-and-effect relationships, to identify the bestperforming leaders, and to determine how those that are currently less successful and lagging behind could progress faster. The authors' previous experiences in using modelling procedures to simulate various socio-economic processes confirms the perspective of such an approach [60,61].…”
Section: Data Mining Algorithms As a Research Toolsupporting
confidence: 57%
“…Algorithms of regression analysis and benchmarking were applied to explore cause-and-effect relationships, to identify the bestperforming leaders, and to determine how those that are currently less successful and lagging behind could progress faster. The authors' previous experiences in using modelling procedures to simulate various socio-economic processes confirms the perspective of such an approach [60,61].…”
Section: Data Mining Algorithms As a Research Toolsupporting
confidence: 57%
“…Several studies conduct country-by-country evaluations, comparing different countries or regions based on the main factors of the DESI index. Karnitis et al [50] compares the Baltic countries with the EU and makes a critical statement on the factors of the DESI index, considering that data mining and mathematical modelling are the main drivers of digitisation. Ershova et al [51] assessed the development of the digital economies of Russia, Ukraine, and developed countries and concluded that digital, technology-driven economies would be the engines of growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Key findings are that Western Balkan economies are generally ready to provide methodologically aligned data for the DESI indicators. Karnitis et al (2019) compared the Baltic countries with the EU. Banhidi et al (2020) investigate the five principal dimensions of DESI using a series of multivariate statistics.…”
Section: Desimentioning
confidence: 99%